An investigation of the effects of submarine groundwater discharge on the coastal carbon and nutrient cycles of a karstic aquifer, Kinvara Bay, Co Galway, Ireland - KELLY, TARA (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2018)
Summary Submarine Groundwater Discharge (SGD) is an important pathway of terrestrial nutrients to the coastal ocean. The influence of SGD on the carbon cycle in coastal zones and the relationship between SGD-borne carbon and other macronutrients remains uncertain. I used a combination of in-situ sampling techniques, experiments with defined conditions and modelling to identify, quantify and characterise SGD-derived carbon and nutrients and assess their biogeochemical importance within coastal zones, using Kinvara Bay, Western Ireland as a case study. Firstly, I used the LOICZ water/salt budget models, and radon analysis where possible, to determine the seasonal SGD rates into the bay. Quantitative nutrient (nitrogen, phosphorus and silica) and carbon budgets were then closed in Kinvara Bay for four sampling campaigns (July 2013, January 2015, June 2015 and January 2016). Across all campaigns, of the three allochthonous carbon and nutrient sources (SGD, raw sewage and wet deposition), SGD was the largest source of carbon and oxidised nitrogen but the lowest source of ammonium and phosphorus into Kinvara bay. Dissolved organic nitrogen (DON) fluctuated significantly from season to season but was highest during the wettest campaign (January 2015). A portion of DON is bioavailable and the DON delivered via SGD contributed to productivity within Kinvara Bay. In terms of whole system N metabolism, the bay was net autotrophic during July 2013, June 2015 and January 2016 but net heterotrophic during January 2015 (the wettest campaign). SGD was the major allochthonous contributor of C to Kinvara Bay. Freshwater SGD delivered elevated concentrations of DIC and comparable concentrations of DOC in comparison to seawater. Whole core sediment incubation experiments confirmed sediment acted as a sink of DOC and as a source of DIC to the bay during June 2015. Closure of the nutrient and carbon budgets confirmed higher primary productivity during July 2013, June 2015 and January 2016 regarding N and C metabolism. Kinvara Bay was net autotrophic and sink for carbon during July 2013, June 2015 and January 2016 but net heterotrophic during January 2015, which was the wettest month and acted as a source of CO2. Ocean acidification is one of the most serious consequences of rising CO2 levels in the atmosphere. The pH of SGD was consistently lower (7.07 - 7.47) than that of oceanic waters (8.1). The role of SGD and its influences on acidification within coastal zones has remained an open question. SGD in karst regions transports large quantities of total alkalinity, which may buffer against acidification but also contains high levels of DIC, which may accelerate acidification. Quantification of the DIC and total alkalinity delivered via SGD to Kinvara Bay indicated that SGD buffered against ocean acidification in Kinvara Bay due to the higher TAlk loading in each sampling campaign. During June 2015, the biological to geochemical ratio was 2.03, calculated from the equation of the line from the plot of TAlk versus DIC. Therefore, SGD may buffer against ocean acidification due to higher TAlk levels in combination with increased metabolism associated with high DIN influxes. Closure of the nutrient and carbon budgets confirmed a productivity-respiration annual cycle in Kinvara Bay, with primary productivity dominating in July 2013, June 2015 and January 2016. Kinvara Bay is currently mesotrophic, however, as future scenarios may lead to eutrophic conditions, continual monitoring of the system is vital as many people rely on it for their livelihoods. SGD delivered a substantially higher N:P ratio than the Redfield Ratio of 16 whilst sewage inputs, although volumetrically small (286 m3 d-1) accounted for 74% of allochthonous P inputs. Mitigation plans for removal of raw sewage may, therefore, further alter the molar and nutrient availability ratios within the bay. As a result, I investigated a future ?what-if? scenario whereby the suspended particulate matter structure within Kinvara Bay changes. A land use change resulting in increased N:P imbalances may lead to a change in the suspended particulate matter within the bay as algae adapt. Species that survive better at altered N:P ratios would be expected to dominate. In this study, Fucus vesiculosus was the dominant macroalgae species at the SGD springs, followed by Enteromorpha intestinalis. Near the sewage outflow point, Ascophyllum nodosum was the dominant species, and both Ascophyllum nodosum and Fucus vesiculosus were found to be significant at the mouth of the bay. These species had high N:P ratios suggesting that they have adapted to survival in an SGD disturbed area. In future scenarios, particularly when Enteromorpha dominated, there was an increased flux of labile materials from the sediment to the water column. As algae function as high-quality food for consumers, productivity within Kinvara Bay would be expected to rise as a result. Increased population and tourism pressures were investigated through increased plastic pollution but did not produce increased refractory or labile components within the water column. This may be due to the types of compounds present in plastic, long organic polymers, which may not be susceptible to degradation or due to the incubation time of five days. Thus, plastic pollution may pose greater influence in the open ocean. A combination of Excitation-Emission Matrix Fluorescence coupled with Parallel Factor Analysis (EEMF-PARAFAC) and Fourier-Transform Ion Chromatography Mass Spectrometry (FT-ICRMS) was employed to characterise chromophoric dissolved organic matter (CDOM) delivered via SGD and its subsequent degradation processes within the coastal zone. SGD was responsible for the delivery of predominately humic-like substances, which were highly refractory. Peak T, a protein-like component, was validated as a secondary component in the 3-component model but with low intensity (0.005 R.U.) This bioavailable component corresponded to spring and was attributed to fertiliser use. In fact, approximately 1% of SGD-borne DOM transported to Kinvara Bay was typically labile, and SGD-borne DOM mainly contributed to C storage within the coastal ocean or was exported to the wider Galway Bay. This pathway may relocate C stocks on land to the sea over time.
APPROVED
Keywords: SGD; Submarine Groundwater Discharge; EEMF-PARAFAC; Chromophoric Dissolved Organic Matter (CDOM); Nitrogen metabolism; Carbon metabolism; Kinvara Bay; FT-ICR-MS; DOM; Ocean acidification